A comparative study on the electrocatalytic and photocatalytic activity of reduced graphene oxide (rGO) and doped rGO based Cu5FeS4 composite. (29th July 2022) - Sebastian, Anju; Deepthi, V.; Sheebha, I.; Vidhya, B.; Maheskumar, V.; Sakunthala, A.
Abstract: Chemical doping of reduced graphene oxide (rGO) oxide has been a major trend as photocatalyst and electrocatalyst owing to large number of active sites they bring in. In the present work ternary copper iron sulphide (Cu5 FeS4 ) has been successfully synthesized using hydrothermal method and incorporated with rGO, N/rGO and B/rGO. The structural, morphological and compositional changes were analyzed using XRD, XPS, SEM, TEM and EDAX results respectively. The bandgap of the materials was confirmed using UV-DRS results. The photoluminescence (PL) spectra of the samples revealed the reduction of recombination with the presence of rGO and doped rGO. The photocatalytic studies of the composites were carried out using methylene blue(MB) as a model pollutant where CFS-N/rGO shows the highest degradation rate of 70%.The electrocatalytic tests were conducted in order to study the performance of the composites as catalyst for HER where CFS-N/rGO showed an enhanced activity with higher current density and lower Tafel slope.The higher Cdl value of CFS-N/rGO indicates the increased number of exposed active sites when doped with N/rGO. The results indicate a considerable amount of change in the photocatalytic and electrocatalytic properties of CFS when doped with rGO, B/rGO and N/rGO. Graphical abstract: Image 1 Highlights: Cu5 FeS4 (CFS) catalyst was prepared via hydrothermal method. The as-synthesized particles were added with rGO, N/rGO and B/rGO (CFS-rGO, CFS N/rGO, CFS-B/rGO). CFS-N/rGO exhibits superior electrocatalytic activity towards HER and photocatalytic activity for dye degradation.